Thermal Performance Analysis of Reinforced Concrete Floor Structure with Radiant Floor Heating System in Apartment Housing - Young-Sun Jeong; Hae-Kwon Jung (Advances in Materials Science and Engineering)
The use of the resilient materials in the radiant floor heating systems of reinforced concrete floor in apartment housing is closely related to the reduction of the floor impact sound and the heating energy loss. This study examined the thermal conductivity of expanded polystyrene (EPS) foam used for the resilient material in South Korea and analysed the thermal transfer of reinforced concrete floor structure according to the thermal conductivity of the resilient materials. 82 EPS specimens were used to measure the thermal conductivity. The measured apparent density of EPS resilient materials ranged between 9.5 and 63.0 kg/m3, and the thermal conductivity ranged between 0.030 and 0.046 W/(m·K). As the density of resilient materials made of expanded polystyrene foam increases, the thermal conductivity tends to proportionately decrease. To set up reasonable thermal insulation requirements for radiant heating floor systems, the thermal properties of floor structure according to thermal insulation materials must be determined. Heat transfer simulations were performed to analyze the surface temperature, heat loss, and heat flow of floor structure with radiant heating system. As the thermal conductivity of EPS resilient material increased 1.6 times, the heat loss was of 3.4% increase.